Genetic Variation Related to High Elevation Adaptation Revealed by Common Garden Experiments in Pinus yunnanensis - Sun, Yan-Qiang; Zhao, Wei; Xu, Chao-Qun; Xu, Yulan; El-Kassaby, Yousry A.; De La Torre, Amanda R.; Mao, Jian-Feng (Frontiers in Genetics, 2020)
Local adaptation, adaptation to specialized niches and environmental clines have been extensively reported for forest trees. Investigation of the adaptive genetic variation is crucial for forest resource management and breeding, especially in the context of global climate change. Here, we set up long-term common garden experiments in high and low elevation sites for Pinus yunnanensis. Significant differences of growth and survival were observed among populations and between common garden sites. By comparing the survival populations between sites, we detected genetic variation related to high elevation adaptation. We captured 103,608 high quality SNPs based on RNA sequencing, and used them to assess the genetic diversity and population structure. We identified 321 outlier SNPs from 131 genes showing significant divergence in allelic frequency between survival populations of two sites. Functional categories associated with adaptation to high elevation were found to be related to flavonoid biosynthesis, response to UV, DNA repair, response to reactive oxygen species, and membrane lipid metabolic process. Further investigation of the outlier genes showed overrepresentation of the flavonoid biosynthesis pathway, suggesting this pathway may play a key role in the adaptation to high elevation in P. yunnanensis. The outlier genes identified in this study, and their variants, provide a basic reference for advanced investigations.